Optimal management of GIST tumors located near the gastroesophageal junction: Case report and review of the literature. (2016) - Ismael, Hishaam; Ragoza, Yury; Caccitolo, James; Cox, Steven
Highlights: There are several endoscopic, laparoscopic and open surgical procedures available for the management of GIST tumors near the GE junction. We present a case-report utilizing both endoscopy and laparoscopy to facilitate resection using the non-touch lesion-lifting technique. Pathology demonstrated a 4.7 cm GIST. The patient was discharged on post-operative day 3 with no complications. We include a full literature review and describe the various combined modalities available for successful resection. Abstract: Introduction: The safety and oncologic outcome of laparoscopic gastric GIST resection is well established especially for lesions <5 cm in diameter. The optimal management of GIST tumors near the GE junction remains unclear. Methods: We present a case-report of a 4.7 cm GIST tumor near the GE junction managed by endoscopically-assisted laparoscopic wedge resection (EAWR). We present a review of the literature highlighting the various combined laparo-endoscopic techniques available. Results: We used the non-touch lesion-lifting method to laparoscopically resect the GIST tumor under endoscopic guidance. There were no complications and the patient was discharged on postoperative day 3. Conclusions: Endoscopically-assisted laparoscopic wedge resections are feasible and safe for GIST tumors near the GE junction.